Aptidão física associada às medidas antropométricas de escolares do ensino fundamental - Andreasi, Viviane [UNESP]; Michelin, Edilaine [UNESP]; Rinaldi, Ana Elisa Madalena; Burini, Roberto Carlos [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2010)
Objective: To analyze associations between health-related physical fitness and the anthropometric and demographic indicators of children at three elementary schools in Botucatu, SP, Brazil. Methods: The sample for this cross-sectional study was 988 elementary school students, recruited from the second to ninth grades (an age range of 7 to 15 years). The children underwent anthropometric assessment (weight, height, waist circumference and tricipital and subscapular skin folds) and were tested for health-related physical fitness (flexibility: sit and reach test; abdominal strength/stamina: 1-minute abdominal test; and aerobic stamina: 9-minute running/walking test). Data were analyzed using descriptive statistics plus Student’s t test, the chi-square test or Fisher’s exact test and logistic regression with a significance level of 5%. Results: The physical fitness levels observed were significantly influenced by age (all levels), sex (abdominal strength/stamina), obesity (all levels), body adiposity (flexibility, abdominal strength/stamina) and abdominal adiposity (abdominal strength/stamina and aerobic stamina). Females were more prone to be unfit in abdominal strength/stamina. Both obesity and excessive abdominal adiposity predisposed children to be unfit in abdominal strength/stamina and aerobic stamina. Excess body adiposity increased the likelihood of poor trunk flexibility. Conclusions: Unhealthy physical fitness levels were related to female sex, obesity and excessive abdominal adiposity. Implementing programs designed to effect lifestyle changes to achieve physical fitness and healthy nutrition in these schools would meet the objectives of promoting healthy body weight and increased physical fitness among these schoolchildren.

Objetivo: Analisar a associação da aptidão física relacionada à saúde com os indicadores demográficos e antropométricos de crianças de três escolas do município de Botucatu (SP). Métodos: A amostra deste estudo transversal foi de 988 escolares do ensino fundamental, do 2º ao 9º ano (faixa etária de 7 a 15 anos). As avaliações realizadas foram antropométricas (peso, estatura, circunferência abdominal e dobras cutâneas tricipital e subescapular) e de aptidão física relacionada à saúde (flexibilidade: teste de sentar e alcançar; força/resistência abdominal: teste abdominal em 1 minuto; e resistência aeróbia: teste de correr/andar por 9 minutos). Para a análise dos dados, utilizou-se estatística descritiva, teste t de Student, qui-quadrado ou exato de Fisher e regressão logística com nível de significância de 5%. Resultados: As aptidões físicas estudadas foram significativamente influenciadas por idade (todas), sexo (força/resistência abdominal), obesidade (todas), adiposidade corpórea (flexibilidade, força/resistência abdominal) e adiposidade abdominal (força/resistência abdominal e resistência aeróbia). O sexo feminino mostrou-se mais propenso à inaptidão de força/resistência abdominal, enquanto que a obesidade e a hiperadiposidade abdominal predispõem os escolares à inaptidão de força/resistência abdominal e resistência aeróbia. O excesso de adiposidade corpórea aumentou as chances de ocorrência da flexibilidade do tronco fraca. Conclusões: As inaptidões físicas foram relacionadas ao sexo feminino, à obesidade e à hiperadiposidade abdominal. Programas de mudança do estilo de vida nas escolas, voltados à aptidão física e à adequação alimentar, preencheriam os objetivos de promoção da eutrofia e da maior aptidão física desses escolares.
Physical fitness and associations with anthropometric measurements in 7 to 15-year-old school children
Keywords: Child; Adolescent; Nutritional status; Healthcare in schools; Criança; Adolescente; Estado nutricional; Saúde escolar